Impact of user-centered water monitoring, prediction and early warning system (et - monitoring) for informed anticipatory action in Borana zone, Ethiopia: Implication for improving pastoral livelihoods and building resilience - Dejene, Sintayehu W.; Alemayehu, Sintayehu; Abdulhamid, Numery; Tegegne, Getachew; Molla, Dessalegn; Tesfaye, Lidiya; Gebre, Liyuneh; Doyo, Jaldesa; Girvetz, Evan (2025)
The User-Centered Water Monitoring, Prediction, and Early Warning System (ET-Monitoring) in Borana Zone, Ethiopia, has played a transformative role in addressing water scarcity challenges. By providing near real-time data on water levels, availability, and waterpoint status, the system has enabled pastoral communities, policymakers, and stakeholders to take informed, anticipatory actions to mitigate the impacts of water shortages. Key interventions, such as relocating livestock to alternative water sources and coordinating emergency water trucking, have significantly reduced livestock losses, maintained livestock health and productivity, and ensured food and water security. The system's success in Borana Zone is evident in various case studies, including Haro Dimitu, Dambi-Korba, Jilo Dhokicha, Liban Jatan, Haro Bake, and Haro Dingamo water points, where early warnings allowed communities to take proactive steps, improving resilience. The system has proven crucial in reducing water scarcity impacts, enhancing livelihoods, and strengthening community resilience. The report highlights the system’s potential for scaling to other pastoral areas in Ethiopia to maximize its impact and build broader climate resilience.